PKM: Pelatihan Perbengkelan Sepeda Motor Bagi Pemuda Karang Taruna Tanggulwangi - Riska Fita Lestari; Lutfi Irawan Rahmat; Adi Mulyadi (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
This article discusses a workshop training for the youth of Karang Taruna Tanggulwangi. Karang Taruna youth do not have permanent jobs and the majority drop out of school. So service training and motorbike repair shop business opportunities are proposed for Karang Taruna Youth, Jambewangi Village, Sempu District, Banyuwangi Regency to reduce the unemployment rate. The results of service training and motorbike repair shop business opportunities can help young people develop employment opportunities related to motorbike service, thereby improving their standard of living.